Marketing Public Relations Kulo Group Dalam Meningkatkan Brand Awareness Pada Kedai Kopi Kulo - Herdian, R Syifa Putri; Delima, Isniyunisyafna Diah; Mirza, Mochammad (Peneliti.net, 2024)
This qualitative research aims to find out about the Kulo group's marketing public relations strategy by increasing brand awareness at the Kulo coffee shop and understanding the obstacles faced by the Kulo Group's Marketing Public Relations in increasing Brand Awereness at the Kulo Coffee Shop. This research method uses descriptive qualitative research methods. Kulo group office research location. The research subjects were the Kulo Group Marketing Public Relations Team, and consumers at the Kulo coffee shop. The theory used is the Three Ways Strategy which includes push, pull, and pass. Data collection techniques used are observation, interviews, documentation. Data analysis techniques by reducing data or summarizing the data obtained, then presenting data that has a relationship with the title and then drawing conclusions. The results of this study indicate that Kedai Kopi Kulo designed a Public Relations strategy to increase brand awareness in accordance with the goals to be achieved and target market segmentation with the Push, Pull and Pass strategy as the strategy. So that makes Kedai Kopi Kulo a coffee brand that is able to develop and compete with other brands.